THE EFFECTIVENESS OF INDIRECT WRITTEN CORRECTIVE FEEDBACK AS PERCEIVED BY TEACHERS AND SECOND YEAR STUDENTS OF MAINSTREAM PROGRAM IN FELTE - ULIS – VNU = HIỆU QUẢ CỦA PHẢN HỒI VIẾT GIÁN TIẾP THÔNG QUA CẢM NHẬN CỦA GIÁO VIÊN VÀ SINH VIÊN NĂM HAI KHOA SƯ PHẠM TIẾNG ANH – TRƯỜNG ĐẠI HỌC NGOẠI NGỮ-ĐẠI HỌC QUỐC GIA HÀ NỘI - Đàm, Mỹ Linh (2020)
The current study investigates the effectiveness of indirect written corrective feedback (WCF) on five different aspects of writing (grammar, language use, mechanic use, content and organization) through the perceptions of teachers and second year students of mainstream program. Specifically, it provides an insight into (1) teachers’ practices in employing indirect WCF to correct students’ writing, (2) teachers’ perceptions of the effectiveness of indirect WCF and (3) second year students’ perceptions of the effectiveness of indirect WCF . To fulfill the stated aims and objectives, this research utilizes two kinds of data collection methods, namely questionnaire and in-depth interview. The combination of both quanitative and qualitative methods enhances the meaningfulness and reliability of the findings.